Left to Our Own Devices. Issue 2 (4th May 2017) - Trub, Leora; Magaldi, Danielle
Abstract : This paper considers the challenges and opportunities presented by computer-mediated treatments made possible by emerging technoculture. Clinical complexities arising from the introduction of screen relations into treatment has changed fundamental assumptions of the analytic situation; these complexities were observed in 26 in-depth interviews conducted with psychoanalytic clinicians on the topic of technology and professional practice. Selected excerpts from these interviews are presented within the context of a broader literature review alongside the authors' theorizing about our current, rapidly changing technological climate. The authors highlight various dimensions of our newfound screen-based analytic relationships such as what the analyst can now "see" through the screen, the realistic and illusory elements of digital space, the "digital third, " and the experience of straddling digital and nondigital realities. A case example is used to illustrate these dimensions and explore implications for analytic process.